Counseling of a Traumatic Theological Student with Involvement in Syncretism: A Traumatology-Case Study to an Indonesian Theological Student - Trihandarkha, Daniel (Sekolah Tinggi Teologi Baptis, Jakarta, 2024)
Indonesian theological students often come to seminary with a handful of problems from the onset of their lives. The expectation from the traditional Christian family for their son and daughters to set the behavior right in the seminary is outdatedly common. This case study explores a 21-year-old theological male student who suffered verbal and physical abuse from his parents. During the initial four weeks of the therapeutic alliance with the author, he exhibits the traumatic symptoms of severe hostility and somatic re-enactment of past adverse experiences. He had been known to possess talismans and some sacred relics for witchcraft in the past, which contemporarily yielded nightmares and terror at night. The qualitative case study explored the traumatic problem of the student through 12 months of observation and in-depth interviews. Through experiential therapy of gestalt, CBT, and forgiveness therapy in the last seven months, the student showed reduced symptoms of hostility, somatic complaints, and impulse behavior. The spiritual formation of prayer and meditating on the Scripture has been seen as valuable by the patient in dealing with his spiritual problems.